Numerical simulation of lubricated DLC-coated point contacts under infinite sliding conditions. (May 2019) - Raisin, Jonathan; Fillot, Nicolas; Vergne, Philippe; Dureisseix, David
Abstract: This article examines the influence of low thermal inertia coatings, such as diamond-like carbon coatings, on the lubrication of point contacts operating under zero entrainment velocity conditions. Stationary thermal elasto-hydrodynamic simulations are performed to analyze modifications to the thermal viscosity wedge mechanism induced by the presence of such coatings. Three configurations, namely a steel-steel contact, a DLC coated steel-DLC coated steel contact and a steel-DLC coated steel contact, are investigated. For each configuration, temperature, pressure and film thickness profiles are presented in order to discuss the tribological performances (film thickness and traction) of low inertia coatings under these very specific lubrication conditions. In particular, the detrimental effect of having only one coated surface is highlighted and explained. Highlights for the manuscript: The thermal viscosity wedge mechanism occurring under zero entrainment velocity conditions can produce strong overpressures. In steel-steel point contacts, these overpressures help maintaining non-zero film thicknesses. Thermally insulating coatings strongly disrupts the thermal viscosity wedge mechanism and hinders the formation of dimples.. Having only one coated surface leads to the lowest minimum film thickness and the highest fluid friction.